Allopurinol-Induced Stevens–Johnson Syndrome in Javanese Men With Positive HLA‐B*58:01 - Ferdiana, Astri; Fachiroh, Jajah; Oktarina, Dyah Ayu Mira; Irwanto, Astrid; Mahendra, Caroline; Febriana, Sri Awalia; Soebono, Hardyanto (Frontiers in Genetics, 2022)
Background: Allopurinol is the most commonly used drug for the treatment of gout arthritis. However, the use of allopurinol is associated with severe cutaneous adverse reactions (SCARs) and life-threatening immune-mediated reactions that include Stevens–Johnson syndrome (SJS). SJS induced by allopurinol is strongly linked with the presence of HLA-B*58:01 in the Asian population. Such a study has not been conducted in Indonesia. We present two cases with clinical diagnosis of SJS. These patients had Javanese ethnicity, for which evidence on the genetic predisposition of allopurinol-induced SJS/TEN had not been established. Testing for the presence of the HLA-B∗58:01 allele was positive in both cases. Our case report confirms findings from studies in Asian countries that link HLA-B*58:01 and allopurinol-induced SJS/TEN. A larger study is needed to elicit evidence that the HLA-B*58:01 allele can potentially be used as a genetic marker for allopurinol-induced SCARs among different ethnicities in Indonesia.